Superoxide dismutase and glutathione reductase overexpression in wheat protoplast: photooxidative stress tolerance and changes in cellular redox state - Melchiorre, Mariana; Robert, German; Trippi, Victorio; Racca, Roberto Walter; Lascano, Hernan Ramiro (Springer, 2021)
In previous works, we have established a correlation between antioxidant system response and tolerance to drought, osmotic stress and photooxidative stress of different wheat cultivars with contrasting drought tolerance. In the present work, a protocol to obtain and transform wheat protoplasts was established. Transgenic protoplasts with Manganese Superoxide Dismutase (Mn-SOD) (E.C.: 1.15.1.1) and Glutathione Reductase (GR) (E.C.: 1.6.4.2) overexpression in chloroplasts were obtained, and their responses to photooxidative stress were characterized. Protoplasts with Mn-SOD or GR overexpression, showed different responses and tolerance to photooxidative stress. Protoplasts with Mn-SOD overexpression showed lower levels of oxidative damage, higher level of endogenous hydrogen peroxide and a great induction of total SOD and GR activities during photooxidative treatments. In protoplasts with GR overexpression the oxidative damage provoked by the photooxidative treatment was similar to control protoplasts, the GSH content and GSH/GSH + GSSG ratio were higher than control and Mn-SOD transformed protoplast, and total SOD and GR activities were not induced. Our results suggest that the differential responses and tolerance to photooxidative stress given by Mn-SOD or GR overexpression, also depend on the effects of these enzyme activities over the cellular redox state balance, which modulate the responses to photooxidative stress.